Effectiveness of New Antifungal Drugs Against Microscopic Fungi Isolated from Agricultural Crops - Pysmenna, Yu.B.; Vortman, M.Ya.; Lemeshko, V.N.; Shevchenko, V.V.; Письменна, Ю.Б.; Вортман, М.Я.; Лемешко, В.Н.; Шевченко, В.В. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
Guanidines are nitrogen-rich organic compounds that have been frequently associated with a wide range of biological activities, such as antibacterial, antiviral, antifungal, and antiprotozoal activities. Guanidinium-containing oligomers based on aliphatic and aromatic oligoepoxides are newly synthesized substances with antifungal activity, providing prospects for their use as agricultural fungicides. Aim. The aim of the study was to investigate the effectiveness of new antifungal drugs against microscopic fungi isolated from agricultural crops and to determine the antagonistic activity of Trichoderma koningii and Trichoderma viride. Methods. The guanidine-containing alkyl-substituted oligomer was obtained through the reaction of the aromatic DER-331 or aliphatic DEG-1 oligoepoxide with guanidine, followed by interaction with alkyl bromides. The fungicidal activity was determined using the agar diffusion method on nutrient media with the following fungal strains: Alternaria alternatа F-41618, Alternaria infectoria F-416121, Aspergillus niger F-41611, Aspergillus flavus F-41612, Acremonium strictum F-41615, Chaetomium globosum F-41617, Сladosporium sphaerospermum F-41623, Botrytis cinerea F-41603, Fusarium poae F-41610, and Fusarium moniliforme F-41605. To compare the effectiveness of the newly synthesized antifungal drugs with existing agents for treating agricultural crops, the following preparations were selected:  "ROYALFLO", "MEDIAN EXTRA", and "STROBI". The determination of interspecies interactions among microscopic fungi was conducted using the agar block method with antagonist cultures isolated from soil, namely Trichoderma viride F-41256 and Trichoderma koningii F-41246. Results. The research results indicate that the newly synthesized fungicidal preparations from the group of guanidine-containing derivatives exhibit moderate fungicidal and fungistatic properties against these representatives of microscopic fungi. Our tests have demonstrated that the most effective biocide is a preparation of tetraalkyl-substituted oligomers based on an aromatic oligoepoxide. The strains of Alternaria infectoria, Aspergillus flavus, Acremonium strictum, Chaetomium globosum, Cladosporium sphaerospermum, and Fusarium moniliforme showed high sensitivity to it, while Alternaria alternata exhibits - medium sensitivity. The strains of Aspergillus niger, Botrytis cinerea, and Fusarium poae displayed low sensitivity. The fungicide "STROBI" demonstrated the highest effectiveness among the biocidal preparations: the size of the growth retardation zone on the 14th day of cultivation decreased insignificantly compared to the other studied preparations. According to the experimental results, Trichoderma koningi exhibited superior antagonistic properties compared to Trichoderma viride. Acremonium strictum was nearly completely suppressed by the block culture Trichoderma viride. Significant fungicidal action with large zones of growth retardation was observed in the test cultures of Alternaria alternata and Cladosporium sphaerospermum. Conclusions. It was found that newly synthesized guanidine-containing preparations exhibited moderate fungicidal and fungistatic properties. Although some drugs available on the market demonstrate much higher efficiency, the investigated compounds show promise due to their specific selectivity of action, especially in cases of resistance formation to other fungicidal drugs. Furthermore, the study demonstrates that the Trichoderma koningii strain exhibits a stronger antagonistic effect on fungi isolated from agricultural crops, offering the potential for the development of an effective antifungal agent.